Blood serum levels of E-cadherin in patients with colorectal cancer - Cepowicz, Dariusz; Zaręba, Konrad; Pryczynicz, Anna; Dawidziuk, Tomasz; Żurawska, Joanna; Hołody-Zaręba, Joanna; Gryko, Mariusz; Kędra, Bogusław (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction : Colorectal cancer is the second most common cancer in terms of incidence in Poland. It is also the second most common cause of cancer deaths in men and the third women. In 75–80% of cases, depending on sources, it is of an occasional nature, and in the remaining 20–25% it has a hereditary character. Aim : To compare the levels of E-cadherin in blood serum with some histopathological and clinical features. E-cadherin is an adhesion molecule, loss of function of which is suspected to influence both cancer progression and metastasis. Material and methods : The study group comprised 48 patients diagnosed with colorectal cancer treated surgically in the Second Department of General and Gastroenterological Surgery, Medical University Hospital in Bialystok. Results : As has been shown here, there is no statistically significant relationship between the levels of E-cadherin in blood serum and the possible prognosis to the progression of colorectal cancer. However, it was indicated that there appears to be a statistically significant relationship between blood serum E-cadherin levels and the levels of alanine aminotransferase and aspartate aminotransferase in patients with colorectal cancer. Conclusions : The authors suggest that this significance may require further study.